2018
DOI: 10.1177/1040638718770490
|View full text |Cite
|
Sign up to set email alerts
|

Development and application of two multiplex real-time PCR assays for detection and speciation of bacterial pathogens in the koala

Abstract: Infectious diseases have contributed to the decline in the health of koala ( Phascolarctos cinereus) populations in the wild in some regions of Australia. Herein we report the development and validation of 2 multiplex real-time PCR (rtPCR) panels for the simultaneous detection of Mycoplasma spp., Ureaplasma spp., Bordetella bronchiseptica, and Chlamydia, including speciation and quantification of Chlamydia, in ocular, reproductive, and nasal swab samples in addition to semen and male urogenital and reproductiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 36 publications
0
33
0
Order By: Relevance
“…Changes in predictive (a) positive and (b) negative values of different noninvasive Chlamydia detection methods as the prevalence of Chlamydia increases (from 5% to 70%) in a population, the methods being the following: qPCR, quantitative Polymerase Chain Reaction as per Hulse et al (), qPCR Wedrowicz based on Wedrowicz et al (); DArTseq, Single Nucleotide Polymorphism using DArTseq method as per Schultz et al () and Detection Dog…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Changes in predictive (a) positive and (b) negative values of different noninvasive Chlamydia detection methods as the prevalence of Chlamydia increases (from 5% to 70%) in a population, the methods being the following: qPCR, quantitative Polymerase Chain Reaction as per Hulse et al (), qPCR Wedrowicz based on Wedrowicz et al (); DArTseq, Single Nucleotide Polymorphism using DArTseq method as per Schultz et al () and Detection Dog…”
Section: Resultsmentioning
confidence: 99%
“…This should be improved in the future by designing specific probes to target chlamydial DNA (such as in Holtz et al, ). Nonetheless, while qPCR outperformed DArTseq, probably because qPCR, contrary to DArTseq, does use Chlamydia ‐specific primers and probes (Hulse et al, ), the sensitivity of qPCR remained low. Applying an occupancy modelling approach to disease prevalence studies, Lachish et al () suggested a protocol of three repeats of qPCR to determine infection status in individuals.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations